A new 128-bit block cipher - Mohd Ali, Fakariah Hani (2009)
The evolvement of technology have resulted in a number of new proposals done on block ciphers such as KAMFEE, KAMKAR, ARIA, BLOWFISH256, DESL, REBC2, DSDP and etc. Even though there have been so much development of the block cipher, the industry still requires another block cipher as long as security features are met. Every country has different requirements when requesting block cipher so there is no limit in developing them. According to the National IT Council (NlTC) report on "Securing Malaysia Sovereignty in the CyberWorld" provided by Ministry of Science, Technology and Innovation, Malaysia, they have outlined critical areas in which new and additional research and development is needed to increase the protection of the national information infrastructure. One of the critical areas is, secured communication which helps to protect the confidentiality and integrity of information during transmission and storage. Secured communication can be achieved by encrypting and hiding data transmission when it is stored on a system. One of the areas which have been identified as priority with respect to secured communications is, conventional cryptography which provides the fundamental security and privacy in the information society. Towards that and after reviewing related research, in this research we propose to come up with a new 128-bit block cipher cryptographic algorithm which shall meet the security requirements. This block cipher uses 128-bit for the key length and block size. It is an involution substitution and permutation encryption network (SPN). This block cipher uses only basic operations, key dependent S-box and XOR IS together so that it can be efficiently implemented on various platforms. The strength of this system is measured by NIST Statistical Test which evaluate from the point of view of the randomness of the block cipher output. From the results, this new block cipher has successfully generated randomness of the block cipher output for data ranging from 1 ,000,000 to 6,000,000 bits. This means that the new block cipher is secured to be used for data ranging from 1 ,000,000 to 6,000,000 bits. This block cipher is suitable to be applied to small devices such as mobile phones and PDAs. The existence of this new 128-bit block cipher algorithm will increase the protection of the national information infrastructure and also will contribute as an alternative to other cryptographic algorithms in security in the computing industry.